2020
DOI: 10.1080/10495142.2020.1760996
|View full text |Cite
|
Sign up to set email alerts
|

“Everyone Should Muck In”: A Qualitative Study of parkrun Volunteering and Conflicting Motivations

Abstract: This study looks at volunteering at parkrun, a weekly 5k run/walk event held at almost 2,000 different locations worldwide, which relies on volunteers. Despite large numbers of parkrunners, and an ethos encouraging occasional volunteering, some parkrunners do not volunteer which can lead to recruitment difficulties for events. Ten parkrunners were interviewed about volunteering to explore why there might be reluctance. Data were transcribed and analysed using thematic analysis, and three interlinked themes fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our findings support previous parkrun volunteering research [13] which showed the primary motive for volunteering was to 'give something back'. Wiltshire and Stevinson [25] explored this through the lens of social capital (the resources and links that derive from contacts in society).…”
Section: Wellbeing Outcomessupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings support previous parkrun volunteering research [13] which showed the primary motive for volunteering was to 'give something back'. Wiltshire and Stevinson [25] explored this through the lens of social capital (the resources and links that derive from contacts in society).…”
Section: Wellbeing Outcomessupporting
confidence: 90%
“…It is possible that RWV balance the cost of volunteering (a median of 2.4 times per year) with the reward of runs (a median of 11.1 times per year). Volunteering for RWV also provided an opportunity to still take part during injury, illness or rest days, which has been found in previous parkrun research [13].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition to physical health benefits, both participants and volunteers gain social network rewards from being part of the parkrun community [5,[21][22][23][24][25][26][27][28]. Engagement with parkrun has also been found to promote a more positive sense-of-self [29].…”
Section: Parkrunmentioning
confidence: 99%